Between two worlds : how the English became Americans - Gaskill, Malcolm (Basic Books, a member of the Perseus Books Group, 2014)
"In Between two worlds, historian Malcolm Gaskill tells the sweeping story of the English experience in America during the first century of colonization. Following a large and varied cast of visionaries and heretics, merchants and warriors, and slaves and rebels, Gaskill illuminates the often traumatic challenges the settlers faced. The first waves sought to re-create the English way of life, even to recover a society that was vanishing at home. But they were thwarted at every turn by the perils of a strange continent, unaided by monarchs who first ignored and then exploited them. As these colonists strove to leave their mark on the New World, they were forced -- by hardship and hunger, by illness and infighting, and by bloody and desperate battles with Indians -- to innovate and adapt, or perish. As later generations acclimated to the wilderness, they recognized that they had evolved into something distinct: no longer just English in America, they were perhaps not even English at all"--Publisher's description